Plainsong - Haruf, Kent (Alfred A. Knopf, 1999)
The interwoven lives of a community in Colorado. The characters include two cattle farmers who take in a girl, thrown out of her house for becoming pregnant. The novel describes the girl's impact on their lives, both men being bachelors.